POLYCYSTIC OVARIAN DISEASE: A DERMATOLOGIST'S VIEWPOINT - Hassan Iffat; Keen Abid (Our Dermatology Online, 2011)
Polycystic ovary syndrome(PCOS) is a common condition characterized by menstrual abnormalities and clinical or biochemical features of hyperandrogenism. Features of PCOS may manifest at any age, ranging from childhood (premature puberty), teenage years (hirsutism, menstrual irregularities), early adulthood and middle life (infertility, glucose intolerance) to later life (diabetes mellitus and cardiovascular disease). Cutaneous manifestations of PCOS are protean and include hirsutism, acne, androgenic alopecia and acanthosis nigricans. Treatment of cutaneous manifestations of PCOS requires a coordinated team approach. A combination of drug therapy, counseling and cosmetic procedures can maximize the results.